SINTASAN Cronobacter sakazakii pGFPuv SELAMA PENYIMPANAN JAGUNG PIPILAN BERKADAR AIR AWAL BERBEDA DI BERBAGAI RH - Karina Nola Sinamo; - Suliantari; Ratih Dewanti-Hariyadi (Jurnal Teknologi dan Industri Pangan, 2016)
Cronobacter sakazakii is an opportunistic foodborne pathogen reported to cause necrotizing enterocolitis, bacteremia, and meningitis in certain groups of infant. C. sakazakii has been reported to survive at low aw or dryness. Presence of wild-type C. sakazakii in dry product is difficult to be distinguished from naturally occuring C. sakazakii. A pGFPuv mutant of C. sakazakii has been reported to have similar growth pattern, thus has the potential to be used in further investigation. The study aimed to evaluate the effect of initial moisture content and relative humidity (RH) on the survival rate of C. sakazakii pGFPuv in corn kernels during storage at room temperature. The study consists of drying corn kernels to achieve moisture contents of 12 and 16% (w.b), inoculation of C. sakazakii pGFPuv, and storage at RH 50, 70 and 90% for 12 weeks. Every two week, corn kernels were sampled and the moisture content was measured using oven method, water activity was measured with aw meter, and total C. sakazakii pGFPuv was enumerated by spread plate method. Meanwhile, total bacteria, mold and yeast were enumerated by pour plate method. Corn kernels achieved equilibrium moisture content and aw after two weeks of storage. The number of C. sakazakii decreased rapidly during storage at RH 70 and 90%, however they could survived at RH 50% for 12 weeks, especially when the initial moisture content was 16%. The total bacteria decreased by 3.5-3.9 Log CFU/g during storage at three RHs, but mold and yeast increased rapidly at RH 90%.